Multisystem inflammatory syndrome in children post-COVID-19: A case report (Indian Journal of Case Reports, 2024)
Multisystem inflammatory syndrome in children (MIS-C) is a complication associated with COVID-19. It is generally characterized by signs of inflammation, including fever and rashes. This is due to neutrophil hyperactivation and leads to a widespread release of inflammatory mediators, which can cause organ damage or even death in severe cases. These symptoms may mimic those of Kawasaki disease, toxic shock syndrome, hemophagocytic lymphohistiocytosis, etc. In this article, we describe one such case of MIS-C of a 21-month-old girl who presented with a high-grade fever of 38.1°C, which was not responsive to antibiotics. She went on to develop rashes on the next day, requiring more workup with detailed history and investigations. We will also discuss the similarities and differences of the mimicking diseases.